Thermal synthesis, characterization and electrochemical study of high-temperature (HT) LiCoO2 obtained from Co(OH)2 recycled of spent lithium ion batteries. (February 2017) - Pegoretti, V.C.B.; Dixini, P.V.M.; Smecellato, P.C.; Biaggio, S.R.; Freitas, M.B.J.G.
Graphical abstract: Highlights: Thermal synthesis of HT LiCoO2 from Co(OH)2 recycled from spent Li-ion batteries. Characterization of recycled HT LiCoO2 by Raman spectroscopy and X-ray diffraction. Characterization of HT LiCoO2 by scanning and transmission electron microscopies. Electrochemical properties of recycled HT LiCoO2 . Abstract: In this work, cobalt has been recycled from a spent lithium-ion battery (LIB) to synthetize high-temperature (HT) LiCoO2 . In the leaching process, the cathode and anode materials are mixed with sulfuric acid and hydrogen peroxide by stirring and heating. The leaching liquor is filtrated to separate the carbon graphite anode. Cobalt hydroxide is precipitated after the addition of potassium hydroxide to the leaching solution. Cobalt hydroxide and lithium carbonate are the precursor materials for the thermal synthesis of HT LiCoO2 at 800 °C for 5 h. The electrochemical behavior of the synthesized material is tested by cyclic voltammetry and cycling tests; the results indicate intercalation and deintercalation of lithium ions into and from the HT LiCoO2 structure. The cathode from the spent LIB and the synthesized material are characterized by X-ray diffraction, Raman spectroscopy with mapping, scanning electron microscopy, and transmission electron microscopy.